Inertial Navigation system of In-pipe Inspection Robot - Al-Masri, Wasim (2016)
A Master of Science thesis in Mechatronics Engineering by Wasim Al-Masri entitled, "Inertial Navigation system of In-pipe Inspection Robot," submitted in May 2016. Thesis advisor is Dr. Mamoun Abdel-Hafez and thesis co-advisor is Dr. Mohammad A. Jaradat. Soft and hard copy available.